Strengthening the Creative Strategic Role In the Dimension of Sustainable Business - Gede Adi Yuniarta; I Gusti Ayu Purnamawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2023)
Most countries and companies always experience a competitive environment, all of which occur due to the development of increasingly capable knowledge and technology, where this is becoming increasingly widespread innovation. This study aims to determine the strengthening of the creative strategic role (dynamic innovation and digital marketing) in sustainable business (competitiveness). This quantitative research method uses primary data obtained from questionnaire data and measured by a Likert scale (1-5). The population of this research is the small business actors in Bali provinces with the lowest economic growth (which has experienced a decline) in Indonesia in 2020-2022. The sample selection used the Slovin formula to obtain a total of 54.489 people, and the research sample obtained is 401 people. Questionnaires as research data were collected and distributed to every small business actor, and data or statistical analysis techniques in the study were considered using the Structural Equation Model (SEM) with WarpPLS 7.0 software modeling. The results of this study show that dynamic innovation and digital marketing have a positive and significant impact on sustainable business.